2010
DOI: 10.1126/scisignal.2000952
|View full text |Cite
|
Sign up to set email alerts
|

Signaling to Transcription Networks in the Neuronal Retrograde Injury Response

Abstract: Retrograde signaling from axon to soma activates intrinsic regeneration mechanisms in lesioned peripheral sensory neurons; however, the links between axonal injury signaling and the cell body response are not well understood. Here, we used phosphoproteomics and microarrays to implicate ~900 phosphoproteins in retrograde injury signaling in rat sciatic nerve axons in vivo and ~4500 transcripts in the in vivo response to injury in the dorsal root ganglia. Computational analyses of these data sets identified ~400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
163
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(167 citation statements)
references
References 65 publications
4
163
0
Order By: Relevance
“…For example, in adult mouse hippocampus, Rest transcripts are upregulated in response to ischemic insult (Kokaia et al, 1994) and are proposed to contribute to cell death through regulation of glutamate excitotoxicity (Calderone et al, 2003). Rest mRNA levels and RE1 occupancy of REST target genes also increase in peripheral neurons in response to nociceptive stimuli (Michaelevski et al, 2010;Uchida et al, 2010;Ben-Yaakov et al, 2012) and have been associated with epilepsy (McClelland et al, 2011;Pozzi et al, 2013). Mechanisms that regulate Rest mRNA levels in these different functional contexts are unknown, but an early study (Kojima et al, 2001) reported that cell type-specific expression of REST was not strictly promoter-dependent, and our studies herein support the suggestion of post-transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in adult mouse hippocampus, Rest transcripts are upregulated in response to ischemic insult (Kokaia et al, 1994) and are proposed to contribute to cell death through regulation of glutamate excitotoxicity (Calderone et al, 2003). Rest mRNA levels and RE1 occupancy of REST target genes also increase in peripheral neurons in response to nociceptive stimuli (Michaelevski et al, 2010;Uchida et al, 2010;Ben-Yaakov et al, 2012) and have been associated with epilepsy (McClelland et al, 2011;Pozzi et al, 2013). Mechanisms that regulate Rest mRNA levels in these different functional contexts are unknown, but an early study (Kojima et al, 2001) reported that cell type-specific expression of REST was not strictly promoter-dependent, and our studies herein support the suggestion of post-transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…PNS injury elicits a dynamic genome response in affected cells reflected in the alteration of hundreds of RNA transcripts in the dorsal root ganglion (DRG). [1][2][3] Whether PNS injury leads to epigenetic remodeling on a grand scale has not been determined but candidate gene studies suggest the possibility. [4][5][6][7] Denk and McMahon 8 suggested in a recent review article that "direct evidence that epigenetic mechanisms could be involved in the development and/or maintenance of chronic pain conditions is only just beginning to surface, and [that] the field is in its infancy;" [that] "the currently available data suggest that epigenetic mechanisms may be important contributors to chronic pain states;" and that "descriptive studies, for instance examination of genome-wide .…”
Section: Introductionmentioning
confidence: 99%
“…Injury discharge and rapid ion fluxes initiate this transition, followed by the loss of target-derived signals and receipt of retrograde signals from the site of injury (8)(9)(10). Retrograde signals include both injury-induced activation and axonal synthesis of intraaxonal transcription factors (TFs) (6).…”
mentioning
confidence: 99%